TOKSISITAS EKSTRAK EKSTRAKSI SERBUK GERGAJI KAYU SENGON LAUT (Albizia falcataria L. Forberg) TERHADAP MORTALITAS Hypothenemus hampei Ferr. (COLEOPTERA: SCOLITYDAE) - Paramita Pratiwi; Rudju Winarsa; Purwatiningsih Purwatiningsih (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract This study was conducted to determine the toxicity of methanol extract SengonSengon SengonSengonSengon wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust wood sawdust againstagainstagainstagainst againstagainst Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different con Hypothenemus hampei. There were 6 different conHypothenemus hampei. There were 6 different concentration centrationcentration centrationcentration centrations of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of extract tested to insect by using contact method. Ten of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 of H. hampei were used for each concentration and replicated 10 times. Mortality insects was recorded 24, 48 and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te and 72 hours. The data was analyzed using GLM (General Linear Model) teand 72 hours. The data was analyzed using GLM (General Linear Model) te st and st and st and st and st and st and Duncan DuncanDuncanDuncanDuncan test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence test at 95% confidence level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of level. Results showed that methanol extract of SengonSengon SengonSengonSengon wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. wood sawdust had significant effect on the mortality of H. hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of hampei after 72 hours. It can be concluded that methanol extract of SengonSengon SengonSengonSengon wood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase thewood sawdust could increase the wood sawdust could increase the wood sawdust could increase thewood sawdust could increase the wood sawdust could increase thewood sawdust could increase the wood sawdust could increase the wood sawdust could increase the wood sawdust could increase thewood sawdust could increase the wood sawdust could increase the wood sawdust could increase the mortality of H. hampei. mortality of H. hampei.mortality of H. hampei. mortality of H. hampei. mortality of H. hampei. mortality of H. hampei.mortality of H. hampei.mortality of H. hampei.mortality of H. hampei.mortality of H. hampei. mortality of H. hampei.Keywords: Hipotenemus hampei, mortality, Sengon wood sawdust, toxcicity.